Study of Indicators for Early and Rapid Diagnosis of Radiation Injury Is the Most Important in Patients With Cancer During Radiotherapy. Issue 1 (26th March 2020) - Liu, Gang; Niu, Li-Mei; Wang, Li-Qin; Li, Ye; Wu, Xiao-Qin; Liu, Yin-Yin; Zhang, Rong
Objective: To establish a complete technical solution for the radiation biological dose estimation, to enable prediction of individuals' response to radiotherapy (RT), and to control treatment dose for reduced irradiation injury and promote repair; and to evaluate the risk of radiation-induced late effects for patients undergoing external photon beam RT and provide the reliable dose–response relationships. Methods: Select 49 tumor patients using 60 Co and linear accelerator for radiation therapy; initial radiation dose was 250 cGy. Chromosome aberration and blood count were analyzed before radiation therapy and 2 hours after the first day of RT. Results: Two hours after the first day of RT, peripheral blood cell count of lymphocytes of patients with cancer was significantly decreased ( P < .01). The frequency of chromosome aberration was higher ( P < .01). Conclusion: High-dose radiation of the radiation therapy makes significant injuries to peripheral blood lymphocytes.